2018
DOI: 10.3389/fpsyg.2018.01166
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships: A Systematic Review on Intimate Partner Violence and Attachment

Abstract: Background: Intimate Partner Violence (IPV) is an important public health challenge. In recent years, there has been a greater awareness concerning this phenomenon, its causes and consequences. Due to the relational nature of IPV, attachment theory (Bowlby, 1988) appears a useful framework to read the phenomenon and to better understand its components and its dynamics to provide more precise and tailored interventions in the future.Purpose: To summarize our knowledge of the research concerning IPV and attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 162 publications
(348 reference statements)
11
99
2
Order By: Relevance
“…This attachment style is termed ‘disorganised’ because the child desperately seeks physical closeness while simultaneously trying to create mental distance. 40,41 A child living in a dysfunctional family system with an abuser or a frightened or frightening caregiver internalises both the caregiver’s feelings of rage, hatred or fear and a frightening or unmanageable self-image. This terrifying self-image, internalised by the child, constitutes a sort of ‘alien self’ or a ‘persecutory object’ that the child must externalise to ‘survive psychically’ and to achieve a bearable and coherent self-representation.…”
Section: Physical and Psychological Violence: Victims Perpetrators Amentioning
confidence: 99%
“…This attachment style is termed ‘disorganised’ because the child desperately seeks physical closeness while simultaneously trying to create mental distance. 40,41 A child living in a dysfunctional family system with an abuser or a frightened or frightening caregiver internalises both the caregiver’s feelings of rage, hatred or fear and a frightening or unmanageable self-image. This terrifying self-image, internalised by the child, constitutes a sort of ‘alien self’ or a ‘persecutory object’ that the child must externalise to ‘survive psychically’ and to achieve a bearable and coherent self-representation.…”
Section: Physical and Psychological Violence: Victims Perpetrators Amentioning
confidence: 99%
“…In addition to the I-Change Model, attachment theory was adopted as a secondary theoretical basis for Dating SOS [34]. Although this theory has been extensively used to explain how attachment may explain the process leading to intimate partner violence [35] and prevention to dating violence [36], its use in CTI to this end has not yet been recorded. The choice of attachment theory to base Dating SOS upon resides in the evidence that adolescents with insecure affective bonding styles tend to use more destructive conflict management strategies and are more frequently victims of dating violence than those securely attached [37,38].…”
Section: Theoretical Basismentioning
confidence: 99%
“…Theoretically, when partners with opposing closeness and distance needs (e.g., insecure anxious and insecure avoidant) or when partners who both desire intense closeness are paired (e.g., insecure anxious and insecure anxious), finding a balancing point may be especially difficult and the attachment system may become aroused frequently (Pistole, 1994; Velotti et al, 2018). In these adult romantic relationships, one or both partners may have experienced attachment injuries, and increased proximity may not elicit the intended safe and secure feeling.…”
Section: Overview Of Attachment Theorymentioning
confidence: 99%
“…Research applying attachment theory to IPV has suggested that it may be the interaction of complementary insecure attachment styles in relationships that triggers violent behavior. For instance, research has found that IPV occurred when the perpetrator was high in attachment anxiety (fearing abandonment) and the other partner was high in attachment avoidance (fearing intimacy; Roberts & Noller, 1998 cited in Allison et al, 2008; Park, 2016; Velotti et al, 2018. Similarly, research has shown that IPV occurs in couples when a male high in attachment avoidance is “mispaired” with a female high in attachment anxiety (Allison et al, 2008; Doumas et al, 2008).…”
Section: Overview Of Attachment Theorymentioning
confidence: 99%